Long-chain omega-3 fatty acids, fish intake, and the risk of type 2 diabetes mellitus(1)(2)(3) - Kaushik, Manas (American Society for Nutrition, 2009)
Background: Diet is a key component of a healthy lifestyle in the prevention of type 2 diabetes mellitus (T2DM). The role of long-chain omega-3 (n–3) fatty acids (LCFAs) in the development of T2DM remains unresolved. Objective: We examined the association between dietary LCFAs and incidence of T2DM in 3 prospective cohorts of women and men. Design: We followed 195,204 US adults (152,700 women and 42,504 men) without preexisting chronic disease at baseline for 14 to 18 y. Fish and LCFA intakes were assessed at baseline and updated at 4-y intervals by using a validated food-frequency questionnaire. Results: During nearly 3 million person-years of follow-up, 9380 new cases of T2DM were documented. After adjustment for other dietary and lifestyle risk factors, LCFA intake was positively related to incidence of T2DM. The pooled multivariate relative risks in 3 cohorts across increasing quintiles of LCFAs were as follows: 1 (reference), 1.00 (95% CI: 0.91, 1.09), 1.05 (95% CI: 0.97, 1.13), 1.17 (95% CI: 1.07, 1.28), and 1.24 (95% CI: 1.09, 1.40) (P for trend < 0.001). Compared with those who consumed fish less than once per month, the relative risk of T2DM was 1.22 (95% CI: 1.08, 1.39) for women who consumed ≥5 servings fish/wk (P for trend <0.001). Conclusions: We found no evidence that higher consumption of LCFAs and fish reduces the risk of T2DM. Instead, higher intakes may modestly increase the incidence of this disease. Given the beneficial effects of LCFA intake on many cardiovascular disease risk factors, the clinical relevance of this relation and its possible mechanisms require further investigation.